A pan-cancer analysis of oncogenic protein tyrosine phosphatase subfamily PTP4As - Mingyang Yu; Chunxu Lin; Min Wei (KeAi Communications Co., Ltd., 2023)
Objective: The objective of this study was to conduct a comprehensive pan-cancer analysis of Protein tyrosine phosphatase 4A (PTP4As), specifically PTP4A1, PTP4A2, and PTP4A3, to investigate their aberrant expression, genomic alterations, prognostic values, and molecular functions. The aim was to evaluate the roles of PTP4As in cancer development and progression, as previous research has primarily focused on PTP4A3 and yielded inconsistent results regarding their expression in cancers. Methods: A meticulous and extensive analysis of PTP4As was performed across diverse cancer types. mRNA expression levels of PTP4A isoforms were examined, and correlations between protein expression and mRNA expression were investigated. Genomic alterations affecting PTP4As, such as amplification, were analyzed. Survival analysis was conducted to assess the prognostic values of PTP4As in different cancers. Additionally, pathway enrichment analysis was performed to identify signaling pathways and biological processes associated with PTP4A2 and PTP4A3. Results: The analysis revealed that PTP4A3 exhibited the most prevalent up-regulation at the mRNA level among the PTP4A isoforms. PTP4A2 mRNA expression in cancer generally displayed an up-regulated trend. However, inconsistent results were observed for PTP4A1 expression, even within the same cancer type but across different datasets, indicating the need for further investigation. The correlation between PTP4As protein expression and mRNA expression was found to be weak, indicating the complexity of their regulatory mechanisms. Genomic analysis showed that amplification was the major type of alteration affecting PTP4As, although it did not always translate into higher expression. Survival analysis revealed that high PTP4As expression was typically associated with unfavorable prognoses in several cancers, although exceptions existed. Pathway enrichment analysis unveiled novel signaling pathways and biological processes potentially influenced by PTP4As. Conclusion: The pan-cancer analysis of PTP4As provided insights into their aberrant expression, genomic alterations, prognostic values, and molecular functions. PTP4A3 exhibited the most prevalent up-regulation, while PTP4A2 showed a general up-regulated trend. Inconsistent results were observed for PTP4A1 expression, warranting further investigation. These findings contribute to our understanding of the molecular mechanisms through which PTP4As may contribute to cancer pathogenesis.